SOME ISSUES OF DISTINCTION OF TOUR OPERATOR’S AND TRAVEL AGENT’S CIVIL LIABILITY - Saghoyan, Eva (State and Law, 2022)
In the article the author discusses gaps of the domestic legislation regulating relationships between tour operator and travel agent and distinction of civil liability thereof. Studying the content and aim of their activities, the author comes to the conclusion that despite the functional and other differences of the mentioned subjects of tourism activity, there are many legal premises for their solidary liability in case of infringement of their obligations, in particular entrepreneurial nature of tourism activity, indivisibility of travel organization service, as well as some obligations of tour agent, notwithstanding the fact, he acts on his own behalf, or on behalf of the tour operator. The author also discusses some issues of collision regulations of civil liability for package tours formed by the foreign tour operators and promoted and realized by domestic tour agents. The author concludes, that if foreign tour operator and domestic tour agent don’t agree otherwise, the law of the Republic of Armenia is applicable to their relationships.